Upaya Meningkatkan Kemampuan Pemahaman Bahasa dengan Menggunakan Media Kartu Kata Bergambar pada Siswa di TK Al-Zaenab Jambangan Surabaya - Rahma, Siti Rochmah; Aida, Nurul; Prayogo, Muhaimi Mughni (Piramida Akademi, 2023)
The ability of early childhood language comprehension is an essential aspect of their cognitive development. This research aims to enhance the language comprehension skills of students at TK Al-Alzaenab Jambangan Surabaya through the implementation of picture card media. The method used is classroom action research (CAR), involving active participation of students in each stage of the learning activities. This research employs a qualitative approach by collecting data through observation, interviews, and documentation. Data analysis used data reduction, data display, and generalization. The research results show a significant improvement in students' language comprehension skills after using the picture card media. This indicates that the media is effective in enhancing language skills in early childhood. The implications of this research can be used as a reference for teachers and educational institutions in designing engaging and effective learning strategies to improve the language comprehension skills of kindergarten children.